Analysis Of Students’ Problem In Speaking English at The Grade XI Of SMK Negeri Pertanian Pembangunan TAPSEL - Huda, Rahmat (Jurnal Hata Poda, 2024)
Abstract The purpose of this study is to identify the issues that students have when communicating in English. Students in grade XI are the subject of this study, which is being conducted using a Descriptive Qualitative Method. Test and interview are used to gather research data. The results show that the students experience a lot of difficulties. The causes of this problem are vocabulary, self-confidence, pronunciation, and anxiety. One of the most important components of the problems that exist is pronunciation, because they are unable to accurately pronounced the use of English Language. Keywords: Speaking